Quality parameter characteristics of tomato powder during strorage at various temperature and packaging materials - Masithoh, Rudiati Evi; Fauzi, Ratyan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2014)
The study aimed at determining color, moisture contents, and soluble solid contents (Brix) of tomato powder stored at various temperature and packaging. Tomatoes were dried at 50 oC then blended as powder. Tomato powder stored for 8 days in various packaging, i.e. aluminium foil, glass bottles, and PE plastic, at various storage temperature, i.e. 5, 15, and 30 oC. Results showed that L color value and Brix decreased while moisture content increased for all storage temperature and packaging. The rate of decrease of L was higher for PE plastic then other packaging. There was a significant effect of storage temperature to moisture contents but no effect of the packaging. Brix decreased insignificantly for all storage temperature and packaging materials.Keywords: Â Tomato powder, Brix, moisture content, L color value